Pengaruh Iklan Media Digital, Kualitas Informasi Dan Kepercayaan Terhadap Keputusan Pembelian Pada Situs E-Commerce Buka Lapak Di Batam - Vira Desnita; Wasiman (Primanomics : Jurnal Ekonomi & Bisnis, 2024)
Indonesian society is increasingly showing a growing interest in the use of online shopping to fulfill their needs and desires, supported by the fact that people now have sufficient understanding and habits regarding the online shopping process. The aim of this research is to determine whether digital media advertising, information quality, and trust have an influence on purchasing decisions. This study uses primary data to prove the hypothesis, collecting data through distributed questionnaires. The population in this research is the community of Batam City with a sample of 100 respondents. The data analysis method employed in this study includes quantitative analysis, descriptive statistical tests, data quality tests, classical assumption tests, influence tests, and hypothesis tests processed using SPSS 27.0 software. Partially, the results of this research indicate that information quality and trust have a positive and significant influence on purchasing decisions, while digital media advertising does not have a significant impact on purchasing decisions. Simultaneously, the research results show that the variables of product design, advertising creativity, and trust have a positive and significant influence on purchasing decisions.